Intubating Conditions and Tracheal Intubation at First Attempt Without Neuromuscular Blockade Using Sevoflurane: Comparison of Clinical Versus Bispectral Index Monitored Depth of Anaesthesia - Amina, Aliyu Husseina; Musa, Usman Yohanna; Barisi, Kpalap Precious; Rimamkanati, Shaki; Thomas, Malau Kefas; Isaiah, Nuhu Samuel; Yammoh, Embu Henry; Suckie, Isamade Erdoo (African Journal of Medicine, Surgery and Public Health Research, 2025)
Tracheal intubation, which is typically made possible by neuromuscular blocking agents, is an essential part of airway management in critical care and anaesthesia. To lessen related side effects such as persistent paralysis, anaphylaxis, and residual neuromuscular blockade, the avoidance of neuromuscular blocking agents is being sought after more and more. This study therefore sought to determine intubating conditions and tracheal intubation at first attempt without neuromuscular blockade using sevoflurane, comparing clinical versus bispectral index monitored depth of anaesthesia. This was a randomised, single-blind, controlled clinical study conducted in the Jos University Teaching Hospital, Jos, Nigeria, among 56 paediatric surgical patients aged 2 to 6 years with ASA I and II scheduled for adenotonsillectomy sampled purposely. Exclusion criteria included parental/guardian refusal, recent respiratory tract infection, and patients with anticipated difficult airway or intubation. Patients were randomised into two groups, B and C, with patients in group B receiving BIS monitoring while those in group C received clinical monitoring for the depth of anaesthesia with sevoflurane and without a neuromuscular blocking agent. After a successful tracheal intubation, the number of attempts at successful tracheal intubation and the intubating conditions scores were noted and recorded for both study groups. Data was analysed using SPSS with students’ t-test and chi-square test being the statistical tests utilised, and the level of significance set at p=0.05. The BIS group had 18 (64.28%), 10 (35.71%), and 0 (0%) children, respectively, with Helbo-Hansen scores of 4, 5, and 6, while the clinical group had 12 (42.86%), 14 (50%), and 2 (7.14%) children, respectively, with similar Helbo-Hansen scores. All the study participants had successful tracheal intubation at the first attempt. The intubating conditions and success rate at the first attempt at intubation when the depth of anaesthesia was monitored using clinical signs compared favourably with when the depth of anaesthesia was monitored using BIS.